2019
DOI: 10.1364/oe.27.001249
|View full text |Cite
|
Sign up to set email alerts
|

A novel methodology to directly pre-determine the relative wavelength response of DFB laser in wavelength modulation spectroscopy

Abstract: A novel methodology to directly predetermine the relative wavelength response (RWR) of a DFB laser, in terms of a combined current linearly scanned wavelength response and current modulated wavelength response (CMWR), in wavelength modulation spectroscopy (WMS) is presented. It is shown that the assessed RWR can be used to mimic the measured response with standard deviation of discriminations that are below 3.4 × 10 −3 cm −1 under a variety of conditions. It is also shown that its performance supersedes two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…where S(T) is the intensity of the characteristic spectral line of the gas, Φ(]) is the lineshape function of the absorbed spectral line, which is described here by the Voigt function, P is the total pressure of the gas, X is the volume concentration of the gas to be measured, and L is the transmission distance of laser in the gas medium, respectively. When the central laser frequency ] 0 is modulated by a sine wave with an angular frequency ω, the instantaneous laser frequency ](t) can be expressed as follows [25,26]:…”
Section: Correction Methodsmentioning
confidence: 99%
“…where S(T) is the intensity of the characteristic spectral line of the gas, Φ(]) is the lineshape function of the absorbed spectral line, which is described here by the Voigt function, P is the total pressure of the gas, X is the volume concentration of the gas to be measured, and L is the transmission distance of laser in the gas medium, respectively. When the central laser frequency ] 0 is modulated by a sine wave with an angular frequency ω, the instantaneous laser frequency ](t) can be expressed as follows [25,26]:…”
Section: Correction Methodsmentioning
confidence: 99%
“…The time‐frequency response relationship (trueν¯()t, bold-italica()t) can be obtained using Fabry–Perot (F–P) interferometer monitoring during the experiments; this is common practice in the TDLAS technique 10–16,23,25 . The absorption harmonic signals can then be simulated accurately.…”
Section: Methodsmentioning
confidence: 99%
“…The time-frequency response relationship (ν t ð Þ, a t ð Þ) can be obtained using Fabry-Perot (F-P) interferometer monitoring during the experiments; this is common practice in the TDLAS technique. [10][11][12][13][14][15][16]23,25 The absorption harmonic signals can then be simulated accurately. The absorption signal includes the integrated absorbance (A) and the line shape derivative ( d kþ2g ϕ dν kþ2g ).…”
Section: Methodsmentioning
confidence: 99%
“…[23,24] In addition, Ma et al have found a method to determine the RWR. [25,26] They have not only considered the linear time-dependent amplitude of the first modulation term but also the constant amplitude of the second modulation term, and this reduced the final scanned-WMS-2 f /1 f fitting residuals significantly. Furthermore, Ma et al proposed a method to pre-determine the RWR, which is based on a second-order polynomial description of the RWR for the ramp-scan current.…”
Section: Introductionmentioning
confidence: 99%